(untitled) (Progressive Agriculture, 2020)
Nitrogen and zinc are essentially required for the growth of wheat and the insufficient amount or inappropriate combination of both may severely reduce the yield. The present investigation was carried out at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh, Bangladesh to evaluate the effect of different levels of nitrogen i.e. 0 kg/ha (control), 60, 120 and 160 kg/ha and zinc i.e. 0 kg/ha (control), 1 and 2 kg/ha and the interactions of nitrogen and zinc on yield and yield contributing traits of Triticum aestivumL. cv. ’Prodip’. The results showed that there were significant differences in yield and yield contributing traits due to the application of N and Zn fertilizers, although some of the yield attributes were non-significant. The maximum plant height (87.67 cm), number of effective tillers plant-1 (3.56), grain yield (5.81 tha-1) and straw yield (7.07 tha-1) were obtained from the application of 160 kg N/ha than at 0/80/120 kg N/ha. Application of 2 kg Zn/ha produced the highest plant height (81.25 cm), number of effective tillers plant-1(3.00), grain yield (5.22 tha-1) and straw yield (6.27 tha-1) whereas, the minimum plant height (80.08 cm), number of effective tillers plant-1(2.58), grain (4.65 tha-1) and straw (5.68 tha-1) yield were found in the control. Interaction effect of N and Zn on yield and most of the yield attributes were found significant. The maximum number of effective tillers plant-1(4.00), grain (6.27 tha-1) and straw (7.40 tha-1) yield were exhibited from the treatment combination of 160 kg N ha-1 + 2 kg Zn ha-1. Grain yield was found to be significantly and positively correlated with number of effective tillers plant-1, number of fertile spikelets spike-1, number of gains spike-1 and straw yield. Therefore, appropriate doses and combinations of nitrogen and zinc would improve the yield of wheat and would provide a rational for the selection of important yield contributing traits for future breeding of wheat for improved yield. Progressive Agriculture 30 (3): 288-297, 2019